Analisis Komprehensif Terhadap Peran Manajer Proyek Dalam Mengelola Proyek Yang Kompleks - Randy Yufid Dika; Muhammad Firza Pahlevi; Aisyah Rahma Agustin (Lembaga Pengembangan Kinerja Dosen, 2023)
A project manager is someone who plays an important role in planning, executing, monitoring, controlling, and also closing a project. This study aims to determine how important the role of the project manager is in managing complex projects. Using the Systematic Literature Review paradigm approach to journals that have been published from 2019 to 2023, the results show that the project manager has an important role in the company. The use of the method for the project manager itself has advantages and disadvantages for each method. Based on the results of this study, the use of the questionnaire filling survey method is the most frequently used project management method. A questionnaire filling survey is collecting data by distributing questionnaires to respondents and asking them to fill them out and return them.